INTEGRATED TRAINING ON HEALTH MANAGEMENT, NUTRITION, REPRODUCTION, AND BREEDING OF GOATS AND SHEEP - Suwarno Suwarno; M. Anam Al Arif; Sri Endah Nurhidayati; Jola Rahmahani; Trilas Sardjito; Rury Mega Wahyuni (LPPM Universitas Flores, 2026)
Community-based goat and sheep farming often faces challenges related to animal health management, feed technology, reproductive management, and breeding practices, which limit livestock productivity. This community service program aimed to improve farmers' knowledge and skills through integrated training covering animal health, feed technology, reproductive technology, and molecular breeding using Polymerase Chain Reaction (PCR). The program was implemented using lectures, interactive discussions, demonstrations, and pretest–posttest evaluations to assess participants' knowledge improvement. The results showed increased knowledge across all training topics. In animal health management, knowledge of infectious diseases, reproductive tract infections, and mineral and vitamin deficiencies increased by 30%, while knowledge of parasitic diseases increased by 20%. Feed technology training improved participants' understanding of agricultural waste utilization and feed fermentation by 10%, while knowledge of nutritional requirements and prevention of postnatal kid mortality increased by 20%. Reproductive technology training resulted in knowledge improvements ranging from 20% to 40%, with the highest increase observed in understanding reproductive organs (40%). In breeding training, knowledge of phenotypic selection increased by 10%, whereas understanding of genotypic selection using PCR increased by 40%. Overall, the integrated training effectively enhanced farmers' knowledge and provided practical skills that support sustainable goat and sheep production. Continuous mentoring and technology adoption are recommended to maximize the long-term impact of the training program on livestock productivity and farmer welfare.